2008
DOI: 10.1124/jpet.107.133546
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term but Not Short-Term p38 Mitogen-Activated Protein Kinase Inhibition Improves Cardiac Function and Reduces Cardiac Remodeling Post-Myocardial Infarction

Abstract: p38 mitogen-activated protein kinase (p38 MAPK) inhibition exerts beneficial effects on left ventricular (LV) remodeling and dysfunction. p38 MAPK activity is transiently increased soon after myocardial infarction (MI), suggesting brief inhibition may afford the same benefit as long-term inhibition. We examined chronic 12-week p38 MAPK inhibition compared with short-term (7-day) inhibition, and then we discontinued inhibition after MI. Post-MI rats at day 7 received either vehicle, 4-[4-(4-fluorophenyl)-1-(3-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 36 publications
(60 reference statements)
1
33
1
Order By: Relevance
“…To date, in vivo studies on the use of p38 inhibitors have been reported with different doses, modes of treatment, duration of treatment, and animal species (Table 3). Many studies have demonstrated the benefit of p38 inhibitors in the in vivo model of sustained ischemia, either in the small animal or large animal model, where p38 inhibitors were found to reduce the infarct size [21,32,68,69] and improve LV function [33,[69][70][71][72][73][74]. Nevertheless, inconsistent reports do exist, mostly from studies performed in the large animal model.…”
Section: Reports Of P38 Inhibitors In An In Vivo Model Of Ischemia/rementioning
confidence: 95%
See 1 more Smart Citation
“…To date, in vivo studies on the use of p38 inhibitors have been reported with different doses, modes of treatment, duration of treatment, and animal species (Table 3). Many studies have demonstrated the benefit of p38 inhibitors in the in vivo model of sustained ischemia, either in the small animal or large animal model, where p38 inhibitors were found to reduce the infarct size [21,32,68,69] and improve LV function [33,[69][70][71][72][73][74]. Nevertheless, inconsistent reports do exist, mostly from studies performed in the large animal model.…”
Section: Reports Of P38 Inhibitors In An In Vivo Model Of Ischemia/rementioning
confidence: 95%
“…Chronic studies investigating the long-term (1-14 weeks) effect of p38 inhibitor in ischemia/reperfusion have been reported. Most of these studies demonstrated that long-term treatment with p38 inhibitors following the induction of myocardial infarction had beneficial effects, such as improved cardiac function [33,[70][71][72][73][74]77], inhibited infarct expansion [33], reduced scar size [77], and suppressed myocardial fibrosis [74].…”
Section: Reports Of P38 Inhibitors In An In Vivo Model Of Ischemia/rementioning
confidence: 98%
“…TAK1/p38α has been specifically implicated in promoting myofibroblast activation; pharmacological inhibition of p38 blunts TGFβ-dependent Acta2 expression and the development of fibrosis in multiple organs, including the heart [9194]. TGFβ stimulation of human dermal fibroblasts also triggers ERK phosphorylation and CTGF expression, which contributes to myofibroblast activation and cytoskeletal rearrangements [95, 96].…”
Section: Transcriptional Regulators Of the Cardiac Fibroblast Phenmentioning
confidence: 99%
“…3, Table 2). Given evidence that p38-MAPK induces cardiac fibrosis and dysfunction [78][79][80] and mediates detrimental remodeling postischemia, 81,82 enhanced postischemic activation may contribute to age-dependent changes in postischemic remodeling. Clinical and experimental data support adverse remodeling in aged myocardium from humans and animal models.…”
Section: Cardioprotective Effects Of Cr In Ma Myocardiummentioning
confidence: 99%